Enhancing the non-technological skills required for effective building information modeling through problem-based learning - Abdul Rahimi, Abdul Rahman; Ayer, Steven K. (International Council for Research and Innovation in Building and Construction, 2019)
Building Information Modeling (BIM) is often associated with the use of new and emerging technologies, but prior research has indicated that non-technological, people- and process-related, issues can hinder the success of BIM even more than the technology itself. Previous work also suggests that analytical and problem-solving, communication, initiative, planning and organizational, and teamwork competencies among construction professionals can help to resolve the most common BIM issues in construction projects. This indicates a new and complementary set of BIM skills that may need to be targeted by educators when preparing students for successful future careers. Previous literature from non-BIM domains suggests that problem-based learning can enhance these types of skills, but there is not an understanding of the extent to which this mode of education can benefit BIM-specific applications. This study aims to analyze the impact of implementing a single-session problem-based learning module that targets the previously identified skills in BIM-relevant contexts. It was found that problem-based learning enabled students to generate better outputs related to solving common issues in BIM-based construction projects. Furthermore, students perceived improvements in their analytical and problem-solving, teamwork, and communications skills after completing the activity. This study adds to the body of knowledge by providing educators with empirical evidence to illustrate how problem-based learning can support BIM education. The lessons from this study could help educators target these same learning benefits in future studies.